Pemanfaatan Mesin CNC Untuk Produksi Cinderamata Guna Meningkatkan Kewirausahaan Masyarakat Binaan Di Masa Pandemi Covid 19 - Afandi Syahputra; Nurmahendra Harahap; Eriansyah Saputra Hasibuan; Donna N. M. Sirait; Dean Timothy Raja; Rizky Aulia Putra (Politeknik Penerbangan Indonesia Curug, 2022)
In this era of very tight competition, every individual must be able to survive in any case, including in the economy. These economic problems make young people especially those who have just finished their education at the SMA/SMK level have to take entrepreneurial steps if there are no job opportunities for them. One of the products in entrepreneurship that still has enthusiasts in the market is souvenirs. In this Community Service, a CNC machine is used for training activities for making souvenirs. It was held at SMK Pulo Brayan Darat (PBD) for 2 days, on December 21 and 22, 2021. On the first day, the participants were given materials and demonstrations by the presenters, and on the second day the participants directly carried out the making of souvenirs. Before carrying out the activity, several stages were carried out such as carrying out observations of the destination of the activity and preparing materials and equipment for the activity, finally after the activity, an evaluation was carried out.. The result of this activity is the creation of several beautiful acrylic souvenirs equipped with colorful lights. Keywords: Acrylic, Entrepreneurship, Souvenirs, Community Service